The Roles of Baitul Maal wat Tamwil in Promoting the Diffusion of Sustainable Financing Innovation: A Narrative Review of the Sharia Business Model - Anom Garbo, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the strategic role of Baitul Maal wat Tamwil (BMT) in the proliferation of sustainable financing innovation in the Islamic microfinance system. Drawing on Islamic ethical norms and local financial organizations, BMTs are strategically positioned to expand inclusive financing products that are responsive to Sharia aims. The goal of this study is to understand how these structures incorporate innovation into their business models with regard to their social and spiritual aims. Adopting a narrative literature review methodology, this study integrates academic publications from Google Scholar and Scopus with the key terms Islamic microfinance, innovation diffusion, and sustainable financing. Based on interdisciplinary approaches, the analysis determines how BMTs promote the adoption and spread of innovation. The findings suggest that BMTs instigate innovation through different channels, including the combination of social and commercial funding, the use of digital platforms, product diversification, stakeholder engagement, and efforts in financial education. These are also intermediaries of morality that mediate between religious duty and adaptive innovation. They support marginalized groups, especially women and microentrepreneurs, by promoting institutional resilience through risk sharing and value-based governance. This study contends that BMTs are of great importance in the reform of Islamic microfinance because they compensate for social and economic gaps as a means to find sustainable and ethical balanced innovations. Implications: This study provides a comprehensive conceptual framework that connects innovation theory and Islamic financial practices, along with empirical insights to direct further research.